2022
DOI: 10.3390/metabo12060517
|View full text |Cite
|
Sign up to set email alerts
|

Untargeted Metabolomics Profiling Reveals Perturbations in Arginine-NO Metabolism in Middle Eastern Patients with Coronary Heart Disease

Abstract: Coronary heart disease (CHD) is a major cause of death in Middle Eastern (ME) populations, with current studies of the metabolic fingerprints of CHD lacking in diversity. Identification of specific biomarkers to uncover potential mechanisms for developing predictive models and targeted therapies for CHD is urgently needed for the least-studied ME populations. A case-control study was carried out in a cohort of 1001 CHD patients and 2999 controls. Untargeted metabolomics was used, generating 1159 metabolites. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…The findings of the meta-analysis included shifts in the levels of branched-chain amino acids, aromatic amino acids, and acylcarnitine. These biomarkers are very similar to those identified in patients diagnosed with coronary heart disease, suggesting a high incidence of cardiovascular disease in the OBM group [ 14 ]. Moreover, the risk of cardiovascular diseases increases with age; therefore, age can influence the OBM group.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The findings of the meta-analysis included shifts in the levels of branched-chain amino acids, aromatic amino acids, and acylcarnitine. These biomarkers are very similar to those identified in patients diagnosed with coronary heart disease, suggesting a high incidence of cardiovascular disease in the OBM group [ 14 ]. Moreover, the risk of cardiovascular diseases increases with age; therefore, age can influence the OBM group.…”
Section: Introductionsupporting
confidence: 68%
“…Amino sugar and nucleotide sugar metabolism pathways are enriched as seen by higher concentrations of glucose, mannose, and fructose in OBM vs. OBO groups. Although changes in arginine and ornithine are not statistically significant, the ornithine to arginine ratio in OBM (1.01) is higher than in OBO (0.88), indicating a shift in nitric oxide production for cardiovascular functions [ 14 ]. Enrichment of fructose and mannose metabolism and galactose metabolism pathways is an indicator of diabetes [ 17 , 18 , 19 ] in the OBM group, which corroborates the clinical data.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding [11] indicated that hypertensive individuals with more severe conditions had lower levels of C22:6 (DHA) acids and triacylglycerols containing C22:5 (DPA), and higher levels of oleic (C18:1) acids. Metabolite risk score was created to evaluate the accuracy of CHD prediction using machine learning and multivariate analysis [13]. Our study has some limitations that need to be highlighted.…”
Section: Discussionmentioning
confidence: 99%
“…The metabolomics characteristics of the enrolled literatures were shown in Table 1. 12 literatures (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) were nally enrolled in this work. Except for two literatures, the samples were urine, and all the other samples were blood.…”
Section: Analysis Of Metabolomics Characteristics Mentioned In the En...mentioning
confidence: 99%